Comparative Efficacy of Valsartan and Valsartan-Hydrochlorothiazide combination Therapy in Hypertensive Heart Disease Patients: a Clinical and Ultrasonographic Study - Ahmad Raza, Muhammad; Ghazanfar, Sidra; Kaleem Akhter, Muhammad; khan, Ghazala; Altuf, Laamia (Journal of Neonatal Surgery, 2025)
Objective: This study aimed to evaluate the clinical efficacy and ultrasound diagnostic outcomes of valsartan combined with hydrochlorothiazide in the treatment of hypertensive patients with heart disease. Material & Methods: A total of 160 patients diagnosed with hypertension and concomitant heart disease who received treatment at Federal Institute of Health Sciences affiliated hospital were enrolled from June 2025 to Sep 2025 and randomly assigned into two equal groups of 80 each. The control group received valsartan monotherapy, while the study group was administered valsartan in combination with hydrochlorothiazide. The therapeutic efficacy and incidence of adverse reactions were compared between the two groups. Results: Results demonstrated that the study group exhibited a significantly higher overall treatment efficacy and a lower rate of adverse reactions compared to the control group (P<0.05). Post-treatment comparisons revealed greater improvements in both systolic and diastolic blood pressure in the study group (P<0.05). Ultrasonic echocardiographic assessments indicated superior recovery in the study group with respect to left ventricular mass index, posterior wall thickness, and ejection fraction (P<0.05). Conclusion: In conclusion, combination therapy with valsartan and hydrochlorothiazide markedly enhances clinical outcomes and reduces adverse events in hypertensive patients with heart disease, supporting its broader clinical adoption..